Minicells as a Damage Disposal Mechanism in Escherichia coli - Camilla U. Rang (American Society for Microbiology, 2018)
ABSTRACT Many bacteria produce small, spherical minicells that lack chromosomal DNA and therefore are unable to proliferate. Although minicells have been used extensively by researchers as a molecular tool, nothing is known about why bacteria produce them. Here, we show that minicells help Escherichia coli cells to rid themselves of damaged proteins induced by antibiotic stress. By comparing the survival and growth rates of wild-type strains with the E. coli ΔminC mutant, which produces excess minicells, we found that the mutant was more resistant to streptomycin. To determine the effects of producing minicells at the single-cell level, we also tracked the growth of ΔminC lineages by microscopy. We were able to show that the mutant increased the production of minicells in response to a higher level of the antibiotic. When we compared two sister cells, in which one produced minicells and the other did not, the daughters of the former had a shorter doubling time at this higher antibiotic level. Additionally, we found that minicells were more likely produced at the mother’s old pole, which is known to accumulate more aggregates. More importantly, by using a fluorescent IbpA chaperone to tag damage aggregates, we found that polar aggregates were contained by and ejected with the minicells produced by the mother bacterium. These results demonstrate for the first time the benefit to bacteria for producing minicells. IMPORTANCE Bacteria have the ability to produce minicells, or small spherical versions of themselves that lack chromosomal DNA and are unable to replicate. A minicell can constitute as much as 20% of the cell’s volume. Although molecular biology and biotechnology have used minicells as laboratory tools for several decades, it is still puzzling that bacteria should produce such costly but potentially nonfunctional structures. Here, we show that bacteria gain a benefit by producing minicells and using them as a mechanism to eliminate damaged or oxidated proteins. The elimination allows the bacteria to tolerate higher levels of stress, such as increasing levels of streptomycin. If this mechanism extends from streptomycin to other antibiotics, minicell production could be an overlooked pathway that bacteria are using to resist antimicrobials.